Enfermedad pélvica inflamatoria como factor de riesgo para el desarrollo de embarazo ectópico - Cava Moreno, Michael Antony (2016)
Objective: Evaluate if pelvic inflammatory disease is a risk factor for the development of ectopic pregnancy. Method: This was an analytic retrospective case-control study in pregnant patients between 18-35 years, with and without medical history of ectopic pregnancy registered in the medical records of the Regional Hospital of Trujillo in the period from 2010 to 2015. A total of 34 cases and 68 controls were included. The data was analyzed in a tetrachoric chart determining the frequency of exposure between cases and controls, the presence of association between Xi square test with 95% confidence and strength of association by Odds Ratio. Results: It was evidenced that 23.5 % of the patients diagnosed with ectopic pregnancy had a medical history of pelvic inflammatory disease (PID), while 5.9 % of the patients without a diagnosis of ectopic pregnancy had a medical history of PID. Xi significance test square was used (with Yates correction) to result 5.2 with p= 0.023 (p< 0.05). It was also obtained an OR of 4.92 (95% CI: 1.36 - 17.77). Conclusions: Pelvic inflammatory disease is a risk factor that raises by 4.92 times the risk of developing an ectopic pregnancy.